Greenwashing in Corporate Climate Claims: Normative Challenges in Indonesian Environmental and Consumer Protection Law - Sahal Hanafi; Nourma Alivia Zahra El Rakhim (Lex Recta: Journal of Law and Normative Justice, 2026)
The proliferation of corporate climate claims in Indonesia has intensified concerns regarding greenwashing and the adequacy of existing legal frameworks in addressing misleading environmental representations. This study examines the normative challenges arising from the interaction between Indonesian environmental law, consumer protection law, corporate governance regulation, capital market law, and sustainable finance instruments. Employing a normative juridical method grounded in doctrinal legal analysis, the research interprets statutory provisions, implementing regulations, and judicial principles through grammatical, systematic, teleological, and comparative approaches. The findings indicate that although multiple legal instruments provide partial bases for sanctioning deceptive climate claims, definitional fragmentation and inconsistent evidentiary standards generate regulatory gaps that weaken enforcement effectiveness. Corporate climate representations should be recognized as legally binding communications subject to verifiability, fiduciary responsibility, and consumer protection standards. An integrated liability framework that harmonizes administrative, civil, and criminal mechanisms is essential to safeguard consumer autonomy, strengthen corporate accountability, and enhance the credibility of national climate governance.